Analysis of solar resources in the wilaya of Msila For the production of green hydrogen - BENNAADJA Oussama; NADJI Aymen; ENCA/Dr. Abderrahim ZEMMIT (Mohamed Boudiaf MSILA University, 2025)
Solar energy is one of the most abundant and sustainable energy sources, playing a crucial role in green hydrogen production. M'Sila, with its geographical location and high solar potential, represents a promising site for solar hydrogen production. This study analyzes solar resources in M'Sila Province to assess their suitability for hydrogen generation. Using HOMER Pro software, we simulate a system integrating a photovoltaic generator and an electrolyzer to evaluate energy performance and economic feasibility. The results provide insights into the seasonal variability of solar resources and highlight the potential of M'Sila as a strategic location for green hydrogen production in Algeria
Keywords: solar energy; hydrogen production; photovoltaic generator; water electrolyzer; HOMER Pro; M'Sila.